Physical and Molecular Characterization of Millet Starches. Issue 3 (14th May 2014) - Annor, George Amponsah; Marcone, Massimo; Bertoft, Eric; Seetharaman, Koushik
ABSTRACT: This study investigated the physical and molecular starch characteristics of four Canadian‐grown millet species: pearl, foxtail, proso, and finger millet. The millet starch granules ranged from about 2.5 to 24 μm in size and were mainly polygonal with a few spherical ones. Their amylose contents ranged from 28.6 to 33.9%, with finger and pearl millets having much more of long amylose chains than short amylose chains compared with foxtail and proso millets. Starches also differed in the molecular structure of their branched amylose, with finger and pearl millets having longer glucan chains between branch points. The enthalpy of gelatinization of starch granules ranged from 11.8 to 13.2 J/g, and the enthalpy of melting of the retrograded starches ranged from 2.2 to 5.9 J/g. The onset temperature of gelatinization ( T o ) of the starches ranged from 62.8 to 70.6°C. Addition of iodine vapor to the granular starches showed significant ( P < 0.05) differences in the ratio of the absorbance to scattering coefficient ( K/S ) values, indicating differences in the rigidity of the glucan chains present in the granules. Starches with short amylose chains exhibited higher K/S values. Iodine vapor addition resulted in altered X‐ray diffractogram peak intensities. The study suggested differences in the structure and granular architecture of the millet starches.